Pengaruh Budaya Organisasi, Modal Intelektual, dan Perilaku Inovatif Terhadap Kinerja Pemimpin Jurusan di Universitas Negeri Medan - Sukarman Purba (KINERJA, 2009)
The  objective  of  this  research  is  to  obtain  information  concerning  the  effect of  organizational culture,  intellectual  capital,  innovative  behavior,  on Department  chairman’s  performance.  The research  was  carried  out  in  2005 with  sample  of  40,  selected  randomly  and the data  has  been analyzed by path  analysis  after  all  variables  put  into  the  correlation  matrix.    The finding of  the research  shows  that  Department  chairman’s  performance  is  affected directly by Organizational culture, Intellectual capital, and Innovative behavior. Based on those findings it could be concluded that any changing or variation which occurred at Department chairman’s performance might have been effected by Organizational  culture,  Intellectual  capital,  and  Innovative  behavior. Therefore,  in  managing Department chairman’s performance, organizational culture, intellectual capital, and innovative behavior should be put into strategic planning of human resources development at Universitas Negeri  Medan,  however other  variables  are  necessary  to  be  taken  into  account  by  next   performance   research.